March of Dimes Report on Access to Maternity Care in the United States. Issue 2 (March 2023) - Simpson, Kathleen Rice
Abstract : In October 2022, the March of Dimes released an updated report on maternity care in the United States focusing on access: Nowhere to Go: Maternity Care Deserts Across the U.S. These data do not reflect favorable conditions for being pregnant, giving birth, or during the first year postpartum in our country. Access to maternity care continues to be a challenge for a significant portion of the childbearing population. A summary of the report is presented. The entire report should be of interest to all who care involved in maternity care in the United States including clinicians, scientists, policymakers, and advocates.